Nanoparticles and nanostructure morphology of a Red Latosol in rehabilitation - Souto Filho,Sebastião N. (2017)
ABSTRACT In the process of rehabilitation of a soil, two points are fundamental: to define optimal interferences to accelerate the rehabilitation process and the most appropriate indicators to diagnose its quality. Therefore, this study aimed to investigate the nanoparticle and nanostructure morphology of a Red Latosol in rehabilitation for eight years. The soil under rehabilitation process was compared with its natural state and degraded. In the topsoil, nanoparticles (ø < 100 nm) and fine clay (ø < 200 nm) were quantified and the nanostructures morphology was studied using images obtained by transmission electron microscopy. Soil porosity, bulk density and carbon, nitrogen and hydrogen contents were analyzed. It was found that the nanoparticles and nanostructure morphology were good soil quality indicators; the physical and chemical attributes were not sensitive to detect alterations between the conditions of degraded soil and soil rehabilitated for eight years; in the class of particles with diameter smaller than 200 nm, for the studied Red Latosol, the visualization of nanostructures is more effective.